Awareness and attitudes towards external auditory canal exostosis and its preventability in surfers in the UK: cross-sectional study. Issue 7 (6th June 2016) - Morris, S; Martin, T; Mccahon, D; Bennett, S
Abstract: Objectives: To determine the proportion of UK surfers aware of external auditory canal exostosis, to identify surfer characteristics associated with knowledge of the condition and to explore attitudes to earplug use. Method: An online, cross-sectional survey of UK-based surfers. Results: Of 375 surfers, 86.1 per cent ( n  = 323; 95 per cent confidence interval = 82.3–89.3) reported awareness of external auditory canal exostosis. Further investigation revealed that, despite their awareness of the condition, 23.4 per cent of these surfers (88 out of 323; 95 per cent confidence interval = 19.5–28.0) had little or no knowledge about external auditory canal exostosis. Predictors of knowledge included: distance from nearest surfing beach ( p  = 0.001), surfing standard (ability) ( p  = 0.008), earplug use ( p  = 0.024) and positive external auditory canal exostosis diagnosis ( p  = 0.009). Conclusion: The findings suggest that a significant minority of UK surfers have no knowledge about this condition. Knowledge of external auditory canal exostosis was significantly associated with earplug use when surfing. Efforts to improve surfers' knowledge are required to enable surfers to better protect themselves, which could reduce the incidence of external auditory canal exostosis.